Adaptivität und semantische Interoperabilität von Manufacturing Execution Systemen (MES) - Schleipen, Miriam (Karlsruher Schriften zur Anthropomatik / Lehrstuhl für Interaktive Echtzeitsysteme, Karlsruher Institut für Technologie ; Fraunhofer-Inst. für Optronik, Systemtechnik und Bildauswertung IOSB Karlsruhe, 2013)
MES (Manufacturing Execution Systems) are situated between automation and management level and are affected from changes of the production. Therefore their adaptivity within the lifecycle of production plants is mission critical. Furthermore MES act as data and information hub. This means that they have to work together with other systems in an efficient and seamless way. MES must be interoperable and must have semantics under control. The present publication faces both aspects.